2004
DOI: 10.2169/internalmedicine.43.209
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis in Inferior Vena Cava (IVC) Due to Intra-cystic Hemorrhage into a Hepatic Local Cyst with Autosomal Dominant Polycystic Kidney Disease (ADPKD)

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…Extra attention should be paid to patients whose symptoms are relative to the severe complications caused by the intracystic hemorrhage. For example, Iguchi et al [5] reported a 76-year-old man with severe edema of both lower extremities and a CT scan revealed an enlarged hemorrhagic hepatic cyst compressing inferior vena cava (IVC) in which massive thromboses formed. Buyse et al [6] reported a patient with simple hepatic cyst developed acute dyspnoea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extra attention should be paid to patients whose symptoms are relative to the severe complications caused by the intracystic hemorrhage. For example, Iguchi et al [5] reported a 76-year-old man with severe edema of both lower extremities and a CT scan revealed an enlarged hemorrhagic hepatic cyst compressing inferior vena cava (IVC) in which massive thromboses formed. Buyse et al [6] reported a patient with simple hepatic cyst developed acute dyspnoea.…”
Section: Discussionmentioning
confidence: 99%
“…For poorly conditioned patients, transcatheter arterial embolization, transhepatic cyst drainage, intracystic ethanol injection or noninvasive methods are indicated. These methods can obtain therapeutic effect in some patients, though the bleeding may recur afterwards [3][4][5]14,15] . Surgery should be performed for most well conditioned patients, especially those whose diagnosis does not preclude malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar fashion, hepatic cysts filled with blood have been reported to result in inferior vena cava thrombosis because of external compression of the vein, in a patient with autosomal dominant polycystic kidney disease and hepatic cystic cavities (22).…”
Section: Discussionmentioning
confidence: 79%
“…Several conditions can result in IVCS, including autosomal dominant polycystic kidney disease, renal cell carcinoma, post-traumatic hematoma and liver abscess. [1][2][3] Congenital liver cysts detected incidentally on ultrasonography or CT are usually asymptomatic and do not require treatment. Cysts can be single or multiple, with sizes ranging from millimeters to 20 cm.…”
Section: Disclosuresmentioning
confidence: 99%